Pioneirismo da Câmara Técnica de Saúde Ambiental do Comitê PCJ na segurança da água - Souza, Roseane Maria Garcia Lopes de; Coneglian, Cassiana Maria Reganhan (International Workshop for Innovation in Safe Drinking Water, 2022)
Sanitation is an essential human right for quality of life and health guarantee for every citizen, regardless of their socioeconomic condition. Everyone has the right to have access to an adequate supply of safe and drinking water. Safe water cannot be sustained only by monitoring its quality, it is necessary to guarantee the supply of water on a continuous basis. The Water Safety Plan carries out a systematic assessment that identifies and characterizes the hazards and risks of water supply systems for human consumption, from the source to the point of delivery, aiming at a preventive risk approach to help guarantee the security of water served to the population, establishing control measures and thereby reducing the burden of diseases related to water supply. The Water Safety Plan is an important instrument for identifying possible deficiencies in the water supply system, organizing and structuring it to minimize the chance of incidents. The Environmental Health Technical Chamber (CT-SAM) of the Piracicaba, Capivari and Jundiaí River Basin Committee (PCJ) has been a pioneer in water security, carrying out actions in the municipalities in order to encourage the implementation of Water Safety Plans to ensure the implementation of the Environmental Health Policy, approved within the scope of the PCJ Committee’s area of ??activity.